A comparative study of short term results of open haemorrhoidectomy and stapler haemorrhoidopexy - Neeralagi, Chandrasekhar S.; Kumar, Yogesh; K. R., Surag; Suggaiah, Lakkanna; Raj, Preetham (International Surgery Journal, 2017)
Background: Haemorrhoids are the most common benign anorectal problems worldwide. Treatments of third and fourth degree hemorrhoids include surgical haemorrhoidectomy. Milligan Morgan haemorrhoidectomy (MMH) as described in 1937 has remained the most popular among many techniques proposed. In order to avoid the postoperative drawbacks of Milligan Morgan haemorrhoidectomy, a new surgical treatment for prolapsing haemorrhoids has been described by Longo in 1995, procedure called stapled haemorrhoidopexy which is associated with less postoperative pain and a quicker recovery. The objective of this study was to compare the short-term outcome between stapled hemorrhoidopexy and Milligan-Morgan hemorrhoidectomy. Methods: Prospective randomized study of 120 patients with grade 3 and grade 4 haemorrhoids requiring surgical treatment either MMH or SH, 60 in each group for the period of 18 months from June 2014 to November 2015. Post-operative pain, duration of surgery, duration of hospital stays, post-operative complications and time taken to return to work were compared with mean follow up period of 6 months. Results: Duration of surgery is significantly low in stapled group with P <0.001, duration of hospital stay is significantly low in stapled group with P <0.001, post-operative pain low in staple group with P <0.05, time taken to return to work is significantly early in stapled group with P <0.001. Post-operative complications incontinence not found in the present study but recurrence of two cases in each group noted. Conclusion: Stapled hemorrhoidopexy is associated with less postoperative pain, shorter duration of surgery and hospital stay, earlier return to work as compared with Milligan-Morgan open hemorrhoidectomy. The procedure is not associated with major post-operative complications.